The Economics of German Unification after Twenty-five Years: Lessons for Korea - Michael C. Burda; Mark Weder (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2017)
This paper reviews the performance of the East German economy in the turbulent quarter-century following reunification and draws some conclusions for the reunification of North and South Korea. In this period, the gap in output per capita between East and West Germany declined at a speed not far from empirical estimates of the neoclas- sical growth model, yet systematic total factor productivity dieren- tials persist despite identical institutional frameworks and significant investment in the eastern regions. At the same time, regional dispar- ities in income, well-being, and health are little dierent from those found within West Germany, and net migration has ceased. On this human metric, German unification has been an unqualified success. For Korea, an eort of this dimension will be costly. A back-of-the- envelope calculation suggests that Korean unification will cost roughly twice as much as its German counterpart.
Keywords: P2; O11; E02; 330; East Germany; convergence; total factor productivity; Korean unification